2015
DOI: 10.1038/srep10859
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting environmental drivers of adult and juvenile growth in a marine fish: implications for the effects of climate change

Abstract: Many marine fishes have life history strategies that involve ontogenetic changes in the use of coastal habitats. Such ontogenetic shifts may place these species at particular risk from climate change, because the successive environments they inhabit can differ in the type, frequency and severity of changes related to global warming. We used a dendrochronology approach to examine the physical and biological drivers of growth of adult and juvenile mangrove jack (Lutjanus argentimaculatus) from tropical north-wes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 35 publications
0
31
0
Order By: Relevance
“…The correlation between ENSO and the LC strength affects species biology and ecology within WA waters. For example, La Niña events have positive impacts on growth rates of fish (Nguyen et al., ; Ong et al., ) and corals (Ong et al., ) and altered the distribution patterns of aggregating whale sharks ( Rhincodon typus ; Anderson et al., ; Wilson, Taylor, & Pearce, ). During the strong La Niña event in summer 2011, there was an extreme warming of SST with anomalies of 2–4 ° C persisting for several months (Pearce & Feng, ), during which ecosystems and marine species were affected (Feng, McPhaden, Xie, & Hafner, ; Smale & Wernberg, ; Wernberg et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between ENSO and the LC strength affects species biology and ecology within WA waters. For example, La Niña events have positive impacts on growth rates of fish (Nguyen et al., ; Ong et al., ) and corals (Ong et al., ) and altered the distribution patterns of aggregating whale sharks ( Rhincodon typus ; Anderson et al., ; Wilson, Taylor, & Pearce, ). During the strong La Niña event in summer 2011, there was an extreme warming of SST with anomalies of 2–4 ° C persisting for several months (Pearce & Feng, ), during which ecosystems and marine species were affected (Feng, McPhaden, Xie, & Hafner, ; Smale & Wernberg, ; Wernberg et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…We used existing detrended (ontogenetic trends removed by dividing the raw series with the mean‐by‐age series) growth increment series for 36 adult mangrove jack ( L. argentimaculatus ) that were collected between 1996 and 2005 at various sites along the NW coast (Fig. ; Ong et al ., ). The detrended increment series from the 36 fish were averaged to obtain a single growth chronology.…”
Section: Methodsmentioning
confidence: 99%
“…Long‐term growth chronologies have already been developed from trees (O'Donnell et al ., ), corals (Cooper et al ., ), and fish (Ong et al ., ) in this region, providing an opportunity to investigate linked biological responses to climate patterns across taxa and ecosystems. These earlier studies have revealed that growth of trees in NW Australia show a strong positive response to rainfall because water is a limiting resource (O'Donnell et al ., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Salinity is an important environmental factor that greatly affects the physiology of marine fish, influencing their survival and distribution12. Some teleosts such as Anguilla anguilla , Sarotherodon melanotheron and Oreochromis niloticus , have a limited capability to endure salinity fluctuation after long-term acclimation345, and are thus restricted in their ability to move between environments.…”
mentioning
confidence: 99%